The Great American Scaffold – Intertextuality and identity in American presidential discourse - Herron, Mark (Tidsskrift for Medier, Erkendelse og Formidling, 2014)
Review of The Great American Scaffold: Intertextuality and Identity in American Presidential Discourse. Frank Austermühl, University of Auckland. John Benjamins Publishing Company, Amsterdam/Philadelphia – 2014.